Metode Tafsir Tahlili Dalam Menafsirkan Al-Qur’an : Analisis Pada Tafsir Ibnu Katsir - Meliani, Fitri; Puspa Rahayu, Tami Dewi; Zulaiha, Eni (AL-IBANAH, 2025)
This journal discusses the Tafsir tahlili method, an approach to interpreting the Al-Qur'an which is based on narration. The tahlili method seeks to analyze and explain the verses of the Al-Qur'an in a whole and comprehensive manner. Explanations include related verse readings, nahwu and nerve structures, the global meaning of a verse, as well as the wisdom of Islamic law and others. Tafsir of the Qur'an using this method is very useful for students of the sciences, and in the world of tafsir using the tahlili tafsir method, there has been a lot of debate among scholars, both for and against it. The research results show that the tahlili Method is a method of interpreting the Al-Qur'an which attempts to explain the Al-Qur'an by describing its various aspects and explaining what is meant by the Al-Qur'an, as well as the existence of limitations, conditions and rules. which must be followed by an interpreter when using the tahlili exegesis method, in order to prevent retention of the original meaning of the Qur'an. In conclusion, Tahlili interpretation plays an important role in enriching understanding of the Al-Qur'an.